Emodin Interferes With Nitroglycerin-Induced Migraine in Rats Through CGMP-PKG Pathway - Sun, Shuding; Zheng, Guo; Zhou, Decui; Zhu, Lili; He, Xin; Zhang, Chunfeng; Wang, Chongzhi; Yuan, Chunsu (Frontiers in Pharmacology, 2021)
The purpose of this study was to explore the effect and mechanism of emodin in interfering with nitroglycerin-induced migraine rats. We carried out behavioral research within 2 h post-nitroglycerin (NTG) injection, and blood samples were collected through the abdominal aorta for measurements of nitric oxide (NO), calcitonin gene-related peptide (CGRP), substance P (SP), tumor necrosis factor (TNF-α) and cyclic guanosine monophosphate (cGMP) levels. Immunohistochemistry was adopted to detect the activation of c-Fos immunoreactive neurons in brain tissues. The number and integrated optical density (IOD) of c-Fos positive cells were measured using Image-Pro Plus. Western blotting was applicated to detect the levels of PKG protein in rat brain tissues. The results showed that emodin can alleviate the pain response of migraine rats and significantly reduce the levels of NO, CGRP, SP, TNF-α and cGMP in migraine rats. In addition, emodin can significantly reduce the number of c-Fos positive cells and the IOD value. Moreover, the expression of PKG protein were significantly inhibited by emodin. Therefore, it is inferred that emodin can relieve migraine induced by NTG through the cGMP-PKG pathway, and can be used as a potential botanical medicine for the treatment of migraine